Borders in cyberspace information policy and the global information infrastructure - Kahin, Brian; Nesson, Charles R. (MIT Press, 1997)
Borders in Cyberspace investigates issues arising from national differences in law, public policy, and social and cultural values in light of the emerging global information infrastructure. The contributions include detailed analyses of some of the most visible issues, including intellectual property, security, privacy, and censorship.
Keywords: Transborder data flow -- Law and legislation.; Online information services -- Law and legislation.; Data protection -- Law and legislation.; Privacy, Right of.; Internet.; Cyberspace.; elektronické knihy; electronic books